A duration dependence test for rational speculative bubbles in the Chinese stock market - Dai, Chichen (2019)
The Chinese stock market suffered from great fluctuation in the past two decades, especially in periods 2006-2008 and 2014-2015. The long increasing stock prices and followed sharp decline arise the suspicion that bubbles exist in the Chinese stock market. Therefore, this dissertation aims to investigate whether these abnormal price movements can be attributed to bubbles.